REPRESENTASI KONTEN BUDAYA LOKAL ACEH DALAM PEMBELAJARAN TEKS NARASI DI UPTD SDN 17 PEUSANGAN - Nabila, Salwa; Nurlaili; Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Narrative text learning in elementary schools is still dominated by teaching materials that do not specifically incorporate Acehnese local culture, resulting in less contextual learning and limited reinforcement of students’ cultural identity. This study aimed to describe the representation of Acehnese local cultural content in narrative text learning, identify how teachers integrate Acehnese local culture into the learning process, and describe students’ responses to local culture-based learning at UPTD SD Negeri 17 Peusangan. This study employed a qualitative descriptive approach involving teachers and students of Grades III, IV, and V as the research participants. Data were collected through observations, interviews, questionnaires, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that the representation of Acehnese local cultural content in narrative text learning remained limited because the teaching materials used had not specifically included narrative texts based on Acehnese local culture. Nevertheless, teachers made efforts to integrate local culture by providing examples, explanations, discussions, and relating the learning materials to students’ daily lives. The integration was carried out by incorporating cultural values, customs, folktales, regional history, and Acehnese traditions into the learning process. In addition, all participating students showed positive responses toward local culture-based learning. The questionnaire results indicated that 100% of the students were more enthusiastic about learning when the narrative texts were related to Acehnese culture because they were considered more interesting, easier to understand, and closely connected to their daily experiences. Therefore, Acehnese local culture has great potential to be integrated into narrative text learning in order to create more contextual and meaningful learning while supporting the preservation of regional cultural heritage.